2005
DOI: 10.1021/bi0479609
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Structural Mechanism of Escherichia coli cAMP Receptor Protein cAMP-Dependent Proteolytic Cleavage Protection and Selective and Nonselective DNA Binding,

Abstract: The Escherichia coli cAMP receptor protein (CRP) displays biphasic characteristics in protease and beta-galactosidase induction assays at increasing cAMP concentrations in response to ligand binding at the secondary binding site located between the primary binding site and the DNA binding domain. Two mutants were created to determine the mechanistic reason for the CRP biphasic response by inhibiting binding of cAMP to the secondary site via interference with the Arg 181 interaction with the ligand's phosphate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 48 publications
3
31
0
Order By: Relevance
“…There are many examples of proteins that bind cGMP with both ligand conformations, "syn" or "anti" (35). Finally, the possibility of the binding of ligands to the secondary cAMP-binding site in CRP is highly unlikely to be relevant to the present study, based on the previously reported requirement for much higher ligand concentrations for binding there (24,34). Taken together, the preserved ligand specificity and shared ligand-binding site in the CRP* variants are internally consistent with the original assumption that the cAMP-binding pocket is not directly altered by CRP* substitutions.…”
Section: Discussionmentioning
confidence: 93%
“…There are many examples of proteins that bind cGMP with both ligand conformations, "syn" or "anti" (35). Finally, the possibility of the binding of ligands to the secondary cAMP-binding site in CRP is highly unlikely to be relevant to the present study, based on the previously reported requirement for much higher ligand concentrations for binding there (24,34). Taken together, the preserved ligand specificity and shared ligand-binding site in the CRP* variants are internally consistent with the original assumption that the cAMP-binding pocket is not directly altered by CRP* substitutions.…”
Section: Discussionmentioning
confidence: 93%
“…Then filling the first C-terminal site inhibits the access to the hinge region and eventually binding of the fourth cAMP decreases selective DNA binding in the lac promoter. 59 However, the current model cannot explain CRP activation at micromolar cAMP concentrations.…”
Section: Resolving the Conformation Of Camp And Current Modelmentioning
confidence: 74%
“…Based on this structure, it is proposed that there are high and low affinity cAMP sites on CRP. [57][58][59] Binding of the first cAMP strongly favors the binding of a second cAMP to high affinity binding sites. At this stage CRP increases its DNA-binding specificity.…”
Section: Resolving the Conformation Of Camp And Current Modelmentioning
confidence: 99%
See 2 more Smart Citations